11.9k views
0 votes
Write the expression for W in terms of K AND write the expression of Z in terms of K PLZ HELP

Write the expression for W in terms of K AND write the expression of Z in terms of-example-1
User Julient
by
6.3k points

1 Answer

7 votes

Answer:


w=100-((100-k)^2)/(100)\\\\z={(100)/(\left(1-(k)/(100)\right)^2) -100

Explanation:


\underline{w \ in \ terms \ of \ z:}


d=\left(1-(k)/(100)\right)c\\a=\left(1-(k)/(100)\right)d\\ \Rightarrow a=\left(1-(k)/(100)\right)^2c...........(1)\\


Again \ a=\left(1-(w)/(100)\right)c...........(2)\\

from equation
(1) and
(2)


\left(1-(k)/(100)\right)^2=\left(1-(w)/(100)\right)\\(w)/(100)=1-\left(1-(k)/(100)\right)^2\\w=100-((100-k)^2)/(100)


\underline{z \ in \ terms \of \ w:}


c=\left(1+(z)/(100)\right)a.......(3)\\

from equation
(1) and
(3)


a=\left(1-(k)/(100)\right)^2\left(1+(z)/(100)\right)a\\\left(1+(z)/(100)\right)=(1)/(\left(1-(k)/(100)\right)^2)\\(z)/(100)=(1)/(\left(1-(k)/(100)\right)^2)-1\\z=100\left[(1)/(\left(1-(k)/(100)\right)^2)-1\right]

User Tim Kamm
by
6.6k points